Sedimentology and history of sediment sources to the NW Labrador Sea during the past glacial cycle. (1st October 2019) - Rashid, Harunur; Piper, David JW.; Drapeau, Julie; Marin, Charlotte; Smith, Mary E.
Abstract: The paleoceanography and sediment dynamics of the northernmost Labrador Sea provides critical records of glacial history, glacially-dominated sedimentation, and paleocirculation. A reference core at 938 m on the SE Baffin Slope was investigated with new oxygen isotope stratigraphy, X-ray fluorescence geochemistry, and 18 14 C-AMS dates and correlated to 14 regional deep-water cores. The reference core provides a paleoceanographic and sediment source record over the last 40 ka, overlying a 3-m-thick blocky mass-transport deposit over MIS 5 autochthonous sediment. Detrital carbonate-rich sediment layers H0-H4, based on bulk geochemistry, were derived principally from Hudson Strait. Shortly after H2 and H3, the shelf-crossing Cumberland Sound ice stream supplied dark brown ice-proximal stratified sediments. Minor supply of carbonate-rich sediment from Baffin Bay allows chronologic integration of the Baffin Bay and Labrador Sea detrital carbonate records and implies an open seaway through Davis Strait. The counterparts of H3, H4, and (?)H5 events in the deep Labrador basin are 4–10 m thick units of thin-bedded carbonate-rich mud turbidites from glacigenic debris flows on the Hudson Strait slope. The behavior of the Hudson Strait ice stream changed through the last glacial cycle. In H1 and H2, the ice stream retreated back across the shelf but did not deglaciate Hudson Bay; in H3–H5 it remained at the shelf break long enough to supply thick turbidites, and subsequent retreat after H4 and H5 deglaciated Hudson Bay. The maximum extent of ice streams in Hudson Strait, Cumberland Sound, and Lancaster Sound was not synchronous. Highlights: New high-resolution SE Baffin Slope sediment facies, geochemistry and δ 18 O record. Chronology of Hudson Strait, Cumberland Sound and Baffin Bay sediment supply. Basinal thick mud turbidites linked to glacigenic debris flows from stable shelf edge ice.